2002
DOI: 10.1126/science.1073823
|View full text |Cite
|
Sign up to set email alerts
|

A Stem Cell Molecular Signature

Abstract: Mechanisms regulating self-renewal and cell fate decisions in mammalian stem cells are poorly understood. We determined global gene expression profiles for mouse and human hematopoietic stem cells and other stages of the hematopoietic hierarchy. Murine and human hematopoietic stem cells share a number of expressed gene products, which define key conserved regulatory pathways in this developmental system. Moreover, in the mouse, a portion of the genetic program of hematopoietic stem cells is shared with embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
1,087
5
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,387 publications
(1,154 citation statements)
references
References 21 publications
44
1,087
5
7
Order By: Relevance
“…Indeed, ES, HSC, and CNS stem cells share more than 200 genes, demonstrating the close relation between these cell types as well as their specific and common features at the transcriptional level. This gene profiling was done by using cDNA arrays for ES cells, gene enrichment for NSC and HSC by using subtractive hybridization (Ivanova et al, 2002;Ramalho-Santos et al, 2002).…”
Section: Can Anything Make Anything?mentioning
confidence: 99%
“…Indeed, ES, HSC, and CNS stem cells share more than 200 genes, demonstrating the close relation between these cell types as well as their specific and common features at the transcriptional level. This gene profiling was done by using cDNA arrays for ES cells, gene enrichment for NSC and HSC by using subtractive hybridization (Ivanova et al, 2002;Ramalho-Santos et al, 2002).…”
Section: Can Anything Make Anything?mentioning
confidence: 99%
“…The reported HSCs gene expression profiles include mouse fetal liver HSCs [41], human and mouse fetal liver HSCs and mouse BM HSCs [42], and mouse BM HSCs [43,44]. The global gene expression profiles of HSCs have identified growth factor receptors, cytokine receptors, hematopoietic growth factor receptors, G-protein coupled receptors (GPCR), morphogen receptors, hormone receptors, and putative genes encoding transmembrane proteins ( Table 2).…”
Section: Global Gene Expression Profiles Of Hscsmentioning
confidence: 99%
“…Corresponding results were reported by [30], in which cat ES-like cells expressed the "stemness" transcription factors and the levels of expression of OCT-4, NANOG and C-MYC were reduced in cat ES-like colonies as compared to that seen in blastocysts. In other study, expression of transcription factors like Oct 4 and Nanog were used as molecular markers for ES cells in various species [16,17,[41][42][43]. Moreover, when undifferentiated primary colonies were analyzed for the expression of pluripotent transcription factors, Gómez et al [30] found that OCT-4 was down regulated regardless of the expression of NANOG.…”
Section: Discussionmentioning
confidence: 99%